State Capacity and Democratic Administration: South Africa’s Post- Democracy View - Mashele Rapatsa (Acta Universitatis Danubius: Administratio, 2016)
State capacity and democratic administration are conceptually distinct, but theoretically interdependent notions whose significance concerning fulfilment of developmental objectives cannot be understated in any democratic dispensation. Thus, this article discusses how the notion of state capacity affect the pursuit of human development and the enforcement and realization of socioeconomic rights under South Africa’s post 1994 democratic dispensation. It is considerate of the fact a progressive fulfilment of people’s socio-economic entitlements largely depends on having a state which has adequate administrative, economic and technical capabilities to discharge its constitutional obligations. Without these capacities, citizens’ legitimate expectations of state fulfilling its obligations as imposed by the Constitution and essential international legal norms diminishes. State capacity is concerned with state’s competence to discharge its governance obligations in pursuit of the goal of regulating and protecting rights and interests of private persons and entities. Weakened state lack capacity to control its functionaries and private agents, consequently depriving citizens of their deserved protection. It is argued that the post 1994 transformative democratic dispensation is caught in a quagmire owing to diminishing fiscal capacity, and is inherently struggling to ward off socioeconomic deprivations inherited from the past.